Protective Effects of Allicin on Acute Myocardial Infarction in Rats via Hydrogen Sulfide-mediated Regulation of Coronary Arterial Vasomotor Function and Myocardial Calcium Transport - Cui, Tianwei; Liu, Weiyu; Yu, Chenghao; Ren, Jianxun; Li, Yikui; Shi, Xiaolu; Li, Qiuyan; Zhang, Jinyan (Frontiers in Pharmacology, 2022)
effective treatments are lacking. Allicin has been reported to have various cardioprotective properties, but its therapeutic effects on AMI have not been elucidated. A rat model of AMI was generated by ligating the left anterior descending branch of the coronary artery. The specific hydrogen sulfide (H2S) synthetase inhibitor, DL-propargylglycine (PAG), was used to examine the effects of allicin on H2S generation. Isolated coronary arteries and cardiomyocytes were assessed for vascular reactivity and cellular Ca2+ transport using a multiwire myography system and cell-contraction-ion detection system, respectively. Allicin administration improved cardiac function and myocardial pathology, reduced myocardial enzyme levels, and increased H2S and H2S synthetase levels. Allicin administration resulted in concentration-dependent effects on coronary artery dilation, which were mediated by receptor-dependent Ca2+ channels, ATP-sensitive K+ channels, and sarcoplasmic reticulum (SR) Ca2+ release induced by the ryanodine receptor. Allicin administration improved Ca2+ homeostasis in cardiomyocytes of rats with AMI by increasing cardiomyocyte contraction, Ca2+ transient amplitude, myofilament sensitivity, and SR Ca2+ content; enhancing Ca2+ uptake induced by SR Ca2+-ATPase and Ca2+ removal induced by the Na+/Ca2+ exchanger; and reducing SR Ca2+ leakage. Notably, the protective effects of allicin were partially attenuated by blockade of H2S production with PAG. Our findings provide novel evidence that allicin-induced generation of H2S mediates coronary artery dilation and regulation of Ca2+ homeostasis in AMI. Our study provides novel mechanistic insight into the anti-AMI effects of allicin and highlight its therapeutic potential for AMI.